2009
DOI: 10.1073/pnas.0811633106
|View full text |Cite
|
Sign up to set email alerts
|

Steroids are required for epidermal cell fate establishment in Arabidopsis roots

Abstract: brassinosteroids ͉ cell fate specification ͉ positional cues ͉ root epidermis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 29 publications
7
82
0
Order By: Relevance
“…4). A model where BES1 acts to boost response to various stimuli is consistent with the role of brassinosteroids in auxin response analyzed here and the observed role of brassinosteroids in enhancing differential cell fate determination during root epidermal development (Kuppusamy et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…4). A model where BES1 acts to boost response to various stimuli is consistent with the role of brassinosteroids in auxin response analyzed here and the observed role of brassinosteroids in enhancing differential cell fate determination during root epidermal development (Kuppusamy et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, a number of experimental studies have shown that the same MYBs-BHLHs-TTG-GL2 network controls epidermal cell fate in both organs (Larkin et al, 2003;Schiefelbein et al, 2003;Serna 2004a;Serna, 2004b). In roots, brassinosteroids also promote root hair formation, acting upstream of the MYBs-BHLHs-TTG-GL2 network (Kuppusamy et al, 2009). Similar to what occurs in the hypocotyl epidermis, the loss of brassinosteroid signalling in the root results in random patterns of GL2 expression and in a strong reduction of CPC expression (Kuppusamy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the overall plant dwarfism, detailed phenotypic analysis has permitted the characterization of tissue-specific defects in plant vasculature Ibañes et al, 2009;Fàbregas et al, 2010), pollen development (Ye et al, 2010), root hair patterning (Kuppusamy et al, 2009), and QC activity (González-García et al, 2011). Signal amplification from the BRI1 receptor implies the transcriptional regulation of thousands of genes that, as direct targets of BES1 and BRZ1, may act in different cell types regulating different responses (Sun et al, 2010;Yu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%